¿Tiene efectos la responsabilidad externa en los indicadores educacionales de los alumnos Un analisis entre los estados de los EE.UU. - Loeb, Susanna (Sociedad y Economía, 2004)
The paper reviews the impact of the implementation of high school student performance evaluation in the different States of the United States. Based on the results of the study, guidelines are offered on the feasibility of this type of evaluations when the improvement of the educational system is at stake, having in mind the variations of this impact according to the population types in which they are applied.